Effect of pinholes in electrolyte on re‐oxidation tolerance of anode‐supported solid oxide fuel cells. Issue 4 (19th August 2021) - Kumada, Keigo; Sato, Kazuhisa; Kawada, Tatsuya; Sumi, Hirofumi; Shimada, Hiroyuki; Hashida, Toshiyuki
Abstract: The effects of through‐thickness pinholes in an electrolyte on re‐oxidation and mechanical damage of anode‐supported solid oxide fuel cells are discussed in this paper. Pinholes with a dimension greater than approximately 10 μm were detected by dye penetrant inspection using half‐cells fabricated through a co‐sintering method. In single cells with such pinholes, the leakage of oxygen occurred through the through‐thickness pinholes under open‐circuit voltage (OCV) conditions when the fuel supply was discontinued. The oxygen leakage caused the oxidation of Ni in the anode, forming semicircular re‐oxidized regions on the electrolyte side of the anode substrate. The oxygen permeation fluxes in the electrolyte, which were deduced from the measured reduction in OCV during the operation of fuel shut‐off, are shown to correlate well with the time elapsed from the shut‐off of the fuel gas supply to the onset of mechanical damage monitored by acoustic emissions. The correlation indicates that the oxidation rate of the anode substrate is accelerated due to the presence of pinholes in the electrolyte, which can result in mechanical damages.